Three-Dimensional Modelling of Computed Tomography Images of Limb Bones in Germany Mast Goose (Anser anser) - Guzel, B. C.; Baygeldi, S. B. (Facta-Fundacio Arnco Ciencia Tecnologia Avicolas, 2023)
The aim of this study is to examine the osteometric measurements of the long and short bones in the fore and hind extremities of German mast geese using 3d reconstruction technique. For this purpose, 10 (5 female and 5 male) German mast goose were used. After the dissection process of the geese was completed, computerized tomography was taken and the reconstruction process was completed. In the measurements made, it was observed that male were longer than female in the GL parameter in all bones. Bd parameter and surface area in the humeral bone were statistically significant (p<0.05). The measurement points of the femur bone were analyzed, statistical significance was found in LM, BP, SC and volume parameters (p<0.05). The parameter Dp was highly significant (p<0.01). As a result, since this study is the first 3D study in geese, it will contribute to the taxonomy and the differences between the birds with the measurements made.
Keywords: 3D modelling; Anatomy; Goose; Reconstruction